Development of a preterm baby – an overview of current knowledge - Młodawska, Marta; Pazera, Grażyna; Młodawski, Jakub (Medical Studies/Studia Medyczne, 2021)
The psychomotor development of children is very important outcome concerning the proper growth and development of a child. We try to eliminate the risk factors that impair its course during intrauterine life, during childbirth, as well as during the first months/years of life, to provide children with optimal conditions for healthy development. Newborns born prematurely are at risk of impaired psychomotor development, including cognitive, neurological, and/or sensory outcomes. The following review presents risk factors that weaken the development of preterm infants, the areas of development in which this weakness may be visible, and methods of evaluation of this development.